2006
DOI: 10.1080/00207140600691344
|View full text |Cite
|
Sign up to set email alerts
|

“How Deeply Hypnotized Did I Get?” Predicting Self-Reported Hypnotic Depth from a Phenomenological Assessment Instrument

Abstract: Procedures for estimating hypnotic depth have been used for more than 70 years. This study predicted self-reported hypnotic depth from the phenomenological and behavioral variables of the Phenomenology of Consciousness Inventory-Hypnotic Assessment Procedure (PCI-HAP). Participants were divided into 2 groups; 1 was used to generate regression equations, and the other group was used for cross-validation. Both imagery vividness during hypnosis (imagoic suggestibility) and the PCI pHGS measure of hypnotic depth (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Prior research (Pekala, Kumar, Maurer, Elliott-Carter, & Moon, 2006) found a correlation between self-reported hypnotic depth and imagoic suggestibility of .72, identical to the present study. However, correlation is not causality, and this hypothesis must await future research.…”
Section: When Including Other Variables In the Regression Equationsupporting
confidence: 87%
“…Prior research (Pekala, Kumar, Maurer, Elliott-Carter, & Moon, 2006) found a correlation between self-reported hypnotic depth and imagoic suggestibility of .72, identical to the present study. However, correlation is not causality, and this hypothesis must await future research.…”
Section: When Including Other Variables In the Regression Equationsupporting
confidence: 87%
“…Hypnosis is a state of consciousness that can be self‐induced or promoted through various procedures (“induction”) enacted by other persons (Elkins et al, 2015). It is described as different from the ordinary state of consciousness (Pekala et al, 2006) and cannot be defined independently from self‐reports, although many cortical correlates have been observed by imaging (Landry et al, 2017; Wolf et al, 2022) and EEG studies (Baghdadi & Nasrabadi, 2012; Hiltunen et al, 2021; Rho et al, 2021; Yargholi & Nasrabadi, 2015). Neutral hypnosis (NH) is a state following hypnotic induction without specific suggestions, that is, requests to imagine perception, memory, and behavior different from the actual ones (for instance, analgesia, hallucination, movement) and to experience them as real and involuntary.…”
Section: Introductionmentioning
confidence: 99%
“…Hypnosis is a state of consciousness which can be self-induced or promoted through various procedures ("induction") enacted by other persons (Elkins et al, 2015). It is described as different from the ordinary state of consciousness (Pekala et al, 2006) and cannot be defined independently from self-reports, although many cortical correlates have been observed by imaging (Landry et al, 2017;Wolf et al, 2022) and EEG studies (Baghdadi & Nasrabadi, 2012;Hiltunen et al, 2021;Rho et al, 2021;Yargholi & Nasrabadi, 2015). Neutral hypnosis (NH) is a state following hypnotic induction without specific suggestions, i.e., requests to imagine perception, memory and behavior different from the actual ones (for instance, analgesia, hallucination, movement) and to experience them as real and involuntary.…”
Section: Introductionmentioning
confidence: 99%